First-principles Insights Into the Structural, Mechanical, Optical, Magnetic, Electronic, and Dynamical Properties of Hf₂CdN MAX phase Compound - Timsina, Suraj; Dhital, Bibek; Shrestha, Sushil; Dhital, Dipesh; Paudel, Ganesh; Rijal, Om Shree; Neupane, Hari Krishna (Api Journal of Science, 2025)
The MAX phase compounds possess both ceramic and metallic properties and have attracted great attention from researchers. In this work, we studied the structural, mechanical, optical, magnetic, electronic, and dynamical properties of the Hf₂CdN MAX phase compound using the density functional theory (DFT) method through the Quantum ESPRESSO as a computational tool. The low value of ground-state energy confirms the structural stability of our compound. The calculated elastic constants of Hf₂CdN satisfy Born’s stability criteria, indicating that it is mechanically stable. Based on the estimated mechanical parameters, Hf₂CdN exhibits anisotropic behavior, metallic-like bonding, and a brittle nature. The phonon frequency curve shows positive values, confirming that the compound is dynamically stable. From the analysis of band structure and density of states (DOS) plots, it reveals that some energy bands cross the Fermi level, indicating metallic behavior. A high absorption coefficient is observed in the visible and UV regions, suggesting potential applications in optoelectronic devices. The strong reflectivity in the UV region further highlights its suitability for radiation shielding and UV mirror materials. Additionally, the high refractive index in the infrared region suggests possible use in optoelectronic applications. From the partial and total, density of states (PDOS and TDOS) analyses, we confirm that Hf₂CdN is nonmagnetic due to the symmetric distribution of spin-up and spin down electron states near the Fermi level. Overall, our findings provide fundamental insights into the properties of Hf₂CdN and its potential applications in various technological fields, such as it would be used in the fields of optoelectronic devices, UV radiation detectors, mirror coatings in UV lasers, and thermal imaging coatings.